Design and manufacturing method of ultra wide band amorphous alloy antenna based on 3D printing

Through additive manufacturing technology based on 3D printing, high-strength amorphous alloy materials are manufactured using the selected laser melting method, which solves the problem of manufacturing high-strength microwave components in low-temperature extreme environments, and realizes the manufacturing of high-reliability ultra-wideband amorphous alloy antennas.

CN119703125APending Publication Date: 2025-03-28XIAN INSTITUE OF SPACE RADIO TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411889018.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to manufacture high-strength and high-reliability microwave components in low-temperature extreme environments, especially in space applications, and traditional processing technology cannot meet the manufacturing needs of complex components.

Method used

Administrative manufacturing technology based on 3D printing is adopted to manufacture high-strength amorphous alloy materials using the selected laser melting method. By optimizing design and process parameters, the integrated manufacturing of ultra-wideband amorphous alloy antenna is realized.

Benefits of technology

The manufacturing of microwave components with high reliability in extreme temperature environments is achieved, which solves the problem that traditional technology cannot meet the manufacturing difficulties of complex components, and improves the structural strength and reliability of components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119703125A_ABST
    Figure CN119703125A_ABST
Patent Text Reader

Abstract

The invention discloses a 3D printing-based ultra-wideband amorphous alloy antenna design and manufacturing method, which comprises the following steps: carrying out space microwave component optimization design for integrated additive manufacturing, taking a dipole emission front end as a representative of an integrated microwave component, and taking a dipole emission front end as a representative of the integrated microwave component; an electric dipole and a magnetic dipole in the antenna are realized by utilizing the combination of the folded arch antenna and the central feed loop antenna; the excitation of an antenna signal is realized through a pair of differential feeds, and a structure which has expandability and is easy to realize by additive manufacturing is provided; the invention discloses a high-strength amorphous alloy implementation technology based on selective laser melting additive manufacturing. The laser power, the scanning speed and the scanning strategy are optimized; angle placement, printing and forming are adjusted according to the structural characteristics of the antenna; and testing the printed amorphous alloy antenna to complete antenna performance verification. The requirements for high strength, high reliability and integration are met, and the high-reliability microwave component integration technology under the space extreme temperature environment is achieved through the amorphous alloy based on the additive manufacturing technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a design and manufacturing method of an ultra-wideband amorphous alloy antenna based on 3D printing. Background Art

[0002] Amorphous alloy (also known as metallic glass) is a new type of metal material developed in the middle of the last century. It has both metal and glass properties and is considered to be a new type of structural material that is pregnant with the third material industrial revolution after steel and plastic. Unlike the periodic long-range ordered atomic structure of traditional metal materials, the atomic structure of amorphous alloys is in a state of short-range order and long-range disorder, so it has a series of mechanical, physical and chemical properties that are significantly better than traditional crystalline alloys. Such as high strength, high elasticity, high toughness, excellent corrosion resistance (corrosion resistance is more than 100 times that of stainless steel) and soft magnetic properties (iron loss is only 1 / 4 of silicon steel), so it has broad application prospects in the fields of machinery, energy, chemical industry and military. Under low temperature conditions, traditional crystalline material specimens will crack, embrittle, movable parts will get stuck, and characteristics will change. These phenomena will cause equipment failure, inability to work normally, and even catastrophic consequences. Therefore, seeking high-performance materials that adapt to extreme low temperature conditions has always been a frontier topic in the field of materials and one of the effective ways to promote the rapid development of related fields. Since the successful development of amorphous alloys, great breakthroughs have been made in their glass-forming ability, thermal stability, microstructure, etc. Unlike traditional crystalline materials, the long-range disorder and short-range ordered microstructure of amorphous alloys determine their unique properties, such as high strength, high hardness, high elastic limit, wear and corrosion resistance, and excellent soft magnetic properties. It is considered to be a very promising structural material.

[0003] Amorphous alloy is a metastable material, which requires a sufficiently high cooling rate during the solidification process from the melt to avoid the formation of a crystalline phase. At present, the preparation methods of amorphous alloys include gas atomization, melt rapid cooling, metal mold casting, etc., but these methods are difficult to achieve the forming and manufacturing of large-sized and three-dimensional complex parts. In addition, amorphous alloys have high strength and high hardness, poor forming and processing performance at room temperature, and are difficult to machine by conventional means. The application of amorphous alloys as structural materials is encountering a bottleneck in forming and manufacturing. Therefore, the development of new forming and manufacturing technologies suitable for three-dimensional amorphous parts has become the key to the future development and application of amorphous alloys.

[0004] The laser additive manufacturing (AM) technology developed in recent years, also known as laser 3D printing (3D Printing) technology, has attracted widespread attention from the scientific community and business, and has become one of the important technologies in the world's development strategy. Compared with traditional subtractive processing and equal material processing and manufacturing methods, additive manufacturing technology is a method based on CAD three-dimensional model files, which melts, solidifies, layers and stacks strips, powders and other materials to build three-dimensional objects from bottom to top. Its technology is more in line with the concept of sustainable development, saving more than double the raw materials, greatly saving processing costs. At present, additive manufacturing technology has been applied to shipbuilding, aerospace, sporting goods, precision instruments, medical equipment and other fields. The principle of selective laser melting additive manufacturing technology is to first lay a layer of powder material to be processed on the substrate, and then use a high-energy density laser or electron beam to scan the layer of powder according to the program. The heated powder material first melts and finally solidifies. Then the substrate is lowered by a layer, and another layer of powder material to be processed is laid on the substrate. Repeat the above steps to finally print the required three-dimensional solid parts. Selective laser melting (SLM) laser 3D printing technology is based on the layer-by-layer accumulation of materials. It can transform complex three-dimensional processing into simple two-dimensional processing, greatly reducing the difficulty of manufacturing complex components. This technology has high forming accuracy and fast cooling speed, and is particularly suitable for the forming and manufacturing of amorphous alloys. It is expected to solve the manufacturing problems of complex components that cannot be completed by traditional processing technologies, and find a new way for the application of amorphous alloys in engineering. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a design and manufacturing method for an ultra-wideband amorphous alloy antenna based on 3D printing. Space microwave payloads will develop in the direction of integration, integration and high reliability. For the extreme temperature environment in space, the spacecraft microwave payload is also required to have high structural strength to meet the challenges of harsh conditions in space; in addition, the integration and high performance of microwave payloads will also lead to the complexity of components, which will further bring reliability problems to the design and implementation of microwave components; therefore, it is urgently necessary to meet the requirements of high strength, high reliability and integration from the component processing itself; in this regard, it is proposed to use amorphous alloys based on additive manufacturing technology to achieve microwave component integration technology with high reliability in extreme temperature environments in space.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:

[0007] A design and manufacturing method of an ultra-wideband amorphous alloy antenna based on 3D printing, comprising the following steps:

[0008] S1, Optimization design of space microwave components for integrated additive manufacturing: The space microwave component is an ultra-wideband antenna, and the structure and thickness of the ultra-wideband antenna are designed and optimized;

[0009] S2, the realization parameters of high-strength amorphous alloys based on selective laser melting additive manufacturing: determine the equipment for additive manufacturing, amorphous alloy powder materials and additive manufacturing substrates, as well as laser power, scanning rate and scanning strategy;

[0010] S3, integration of amorphous alloy ultra-wideband antenna: adjust the angle and place the antenna according to its structural characteristics and print it;

[0011] S4, 3D printed amorphous alloy ultra-wideband antenna test verification: Perform structural tests, amorphous rate tests, electrical performance tests, and high and low temperature electrical performance tests on the printed amorphous alloy antenna to complete antenna performance verification.

[0012] The present invention also includes the following technical features:

[0013] Specifically, in S1, the ultra-wideband antenna includes a folded bow structure and a central feeding ring;

[0014] The folded arched structure serves as an electric dipole, comprising two inclined plane parts symmetrically distributed on the left and right and horizontal parts connected to the distal ends of the two inclined plane parts, wherein the connection between the horizontal part and the inclined plane part is the downwardly inclined end of the inclined plane part;

[0015] The central feeding ring serves as a magnetic dipole and includes two short-circuit walls, a ground between the two short-circuit walls, and the bottom surfaces of the two inclined portions; the short-circuit wall is connected to the lower end where the inclined portion and the horizontal portion meet, and the two short-circuit walls are opposite to each other.

[0016] Specifically, the thickness of the folded arch structure is 1 mm.

[0017] Specifically, in S1, the ultra-wideband antenna is excited by a pair of differential feed lines, which are composed of two sections of 50-Ω microstrip lines and a tapered parallel strip transmission line; one end of each 50-Ω microstrip line is connected to an SMA connector, and the other end is connected to the tapered parallel strip transmission line; the tapered parallel strip transmission line realizes an impedance transformer between 100Ω and 212Ω.

[0018] Specifically, in S2, the additive manufacturing equipment uses SLM metal laser additive manufacturing equipment, which uses a 200W continuous laser, the galvanometer scanning system is a three-axis high-precision scanning galvanometer, and the laser is controlled by digital signals. The laser spot diameter is 20 to 100 μm and the maximum scanning speed is 15 m / s.

[0019] Specifically, in S2, the amorphous alloy powder material is a zirconium-based amorphous alloy Zr41.2 Ti 13.8 Cu 12.5 Ni 10 Be 22.5 Powder, D 50 =15-53μm.

[0020] Specifically, in S2, the additive manufacturing substrate is a metal zirconium plate.

[0021] Specifically, in S2, the laser power is 90 W, the scanning rate is 1000 mm / s, and the inter-layer scanning angle is 0°.

[0022] Specifically, in S3, the ultra-wideband antenna is printed at an angle of 45°.

[0023] Specifically, the S4 includes: using an optical scanning measurement system to test the dimensional accuracy of the printed amorphous alloy antenna; using a D8 ADVANCE A25 X-ray diffractometer to detect the amorphous rate of the printed amorphous alloy antenna, with a scanning step of 0.02°, a scanning speed of 1° per minute, and a scanning range from 20° to 90°; using a dual cable connection to test the electrical properties of the printed amorphous alloy antenna; using DELTA9023 to test the conductivity of the printed amorphous alloy antenna in five temperature environments of -120°C, -50°C, 0°C, 100°C, and 170°C.

[0024] Compared with the prior art, the present invention has the following technical effects:

[0025] The present invention carries out an optimized design of space microwave components for integrated additive manufacturing, and provides a structure that is scalable and easy to implement with additive manufacturing.

[0026] The present invention uses an amorphous alloy based on additive manufacturing technology to achieve a microwave component integration technology with high reliability in extreme temperature environments in space. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a flow chart of the method of the present invention.

[0028] Figure 2 It is a schematic diagram of the ultra-wideband antenna structure.

[0029] Figure 3 This is a schematic diagram of the ultra-wideband antenna structure optimized for the present invention.

[0030] Figure 4 It is a Zr-based amorphous ultra-wideband antenna component printed by SLM.

[0031] Figure 5 It is the dimensional accuracy measurement of ultra-wideband antenna components.

[0032] Figure 6 It is the echo and voltage standing wave ratio of the amorphous alloy antenna.

[0033] Meaning of reference numerals:

[0034] 1. Folded bow-shaped structural member, 2. Central feed ring, 3. Box-type reflector, 11. Inclined part, 12. Horizontal part, 21. Short-circuit wall. DETAILED DESCRIPTION

[0035] The present invention provides a design and manufacturing method of an ultra-wideband amorphous alloy antenna based on 3D printing. The method first carries out an optimized design of space microwave components for integrated additive manufacturing, and provides a structure that is scalable and easy to implement for additive manufacturing. Then, based on the high-strength amorphous alloy implementation technology of selective laser melting additive manufacturing, the amorphous alloy is implemented and optimized under different SLM processes. On this basis, the integrated implementation and performance characterization of amorphous alloy space microwave components are completed. Finally, the stability of amorphous alloys under extreme temperature changes is explored.

[0036] More specifically, this method uses a dipole transmitting front end as a representative of an integrated microwave component, and utilizes a combination of a folded bow antenna and a center-fed loop antenna to realize the electric dipole and magnetic dipole in the antenna. In addition, a pair of differential feeds are used to realize the excitation of the antenna signal, providing scalability and a structure that is easy to implement with additive manufacturing. At the same time, the design of the components for 3D printing is optimized: the side walls of the substrate are removed, and the thickness of the butterfly-shaped electric wall is optimized. Secondly, based on the high-strength amorphous alloy implementation technology of selective laser melting additive manufacturing, the laser power, scanning speed and scanning strategy are optimized. Then, the antenna is placed at a certain angle for printing and forming according to its structural characteristics. Finally, the printed amorphous alloy antenna is subjected to structural testing, roughness characterization, electrical performance testing, and low-temperature characteristics testing to complete the antenna performance verification.

[0037] The present invention provides a design and manufacturing method for an ultra-wideband amorphous alloy antenna based on 3D printing, such as Figure 1 As shown, the following steps are included:

[0038] S1, carry out optimization design of space microwave components for integrated additive manufacturing:

[0039] The spatial microwave component is an ultra-wideband antenna, and the structure and thickness of the ultra-wideband antenna are designed and optimized; taking the dipole transmitting front end as the representative of the integrated microwave component, a combination of a folded bow antenna and a center-fed loop antenna is used to realize the electric dipole and magnetic dipole in the antenna; at the same time, the antenna signal is excited by a pair of differential feeds, providing scalability and a structure that is easy to realize by additive manufacturing; and optimizing the structure and thickness of the dipole antenna.

[0040] Specifically, in S1, the ultra-wideband antenna includes a folded bow structure 1, a central feeding ring 2 and a box-type reflector 3, such as Figure 2 shown.

[0041] The folded arch structure 1 serves as an electric dipole, and includes two symmetrically distributed inclined portions 11 and horizontal portions 12 connected to the distal ends of the two inclined portions 11 . Specifically, the connection between the horizontal portion 12 and the inclined portion 11 is the downwardly inclined end of the inclined portion 11 .

[0042] The center feed loop 2 acts as a horizontal magnetic dipole, including two short-circuit walls 21, the ground between the two short-circuit walls 21, and the bottom surfaces of the two inclined portions 11; the short-circuit wall 21 is connected to the lower end of the junction of the inclined portion 11 and the horizontal portion 12, and the two short-circuit walls 21 are opposite. The center feed loop 2 is used as a magnetic dipole in the antenna. The size of this loop is larger than that of a traditional short-circuited patch antenna and provides a wider impedance bandwidth. If there is no short-circuit, the loop cannot be constructed, and the antenna is just a folded bow antenna. For antennas with short-circuit, the radiation patterns of the E and H planes become more consistent, and the back radiation level is significantly reduced. The reason is that the center feed loop cooperates with the folded bow structure to realize the ME dipole antenna, which usually provides more identical patterns and low back radiation levels on the E and H planes.

[0043] The electric dipole and magnetic dipole are excited at the same time, realizing a magneto-electric dipole antenna.

[0044] A folded arch structure 1 and a central feeding ring 2 are placed in the box-shaped reflector 3 to reduce the fluctuation of the antenna gain at the operating frequency, especially at high frequencies.

[0045] Considering the particularity of the 3D printing process, the processing and molding is carried out in a layer-by-layer stacking manner. Therefore, two issues need to be considered: First, the design of support molding. Although for antennas without inner cavities, self-support molding can be considered, too much support structure will still lead to poor molding quality, roughness of the support surface, and reduced electrical performance. Therefore, how to reduce the impact of support assistance is one of the goals of design optimization. In addition, the thickness of the folded bow structure of the ultra-wideband antenna must also be considered, because the molding quality of the 3D printing process is also affected by the printing thickness, so this part is also a factor that needs to be considered.

[0046] During the printing process, it was found through multiple printing iterations that although the box-shaped reflector has a certain effect on the antenna radiation performance, it will greatly affect the molding quality. Therefore, the box-shaped reflector was removed. The four side walls of the box-shaped reflector 3 can be removed. In addition, due to the idealization of the point boundary in the model, it is actually impossible to set the folded bow structure 1 to a micro-ideal thickness. According to the results of multiple printing iterations, the optimized design is 1mm. The overall structure after optimization is shown in the figure below: Figure 3 shown.

[0047] The ultra-wideband antenna is excited by a pair of differential feed lines, which consist of two sections of 50-Ω microstrip lines and a tapered parallel strip transmission line; one end of each 50-Ω microstrip line is connected to an SMA connector and the other end is connected to a tapered parallel strip transmission line; the tapered parallel strip transmission line implements an impedance transformer between 100Ω and 212Ω. Due to the use of a tapered parallel strip transmission line, it can be considered as an infinitely large virtual ground plane placed in the middle of the parallel strip lines. Two rectangular metal patches close to the feed lines are used in the design as its ground plane. Therefore, the entire feed structure is a multi-layer structure, which increases the complexity of antenna manufacturing.

[0048] S2, high-strength amorphous alloys based on selective laser melting additive manufacturing parameters:

[0049] Determine the equipment, amorphous alloy powder materials and AM substrate for AM, as well as laser power, scan rate and scanning strategy.

[0050] Specifically, in S2, the additive manufacturing equipment uses SLM metal laser additive manufacturing equipment, which uses a 200W continuous laser, and the galvanometer scanning system is a three-axis high-precision scanning galvanometer. The laser is controlled by a digital signal, the laser spot diameter is 20 to 100μm, and the maximum scanning speed is 15m / s; the molding cylinder size is a Φ150mm cylindrical molding cylinder, the molding height is 200mm, the powder layer thickness is 0.02 to 1.00mm adjustable, the powder feeding method is one-way powder feeding, and the parameters can be modified online in real time. At the same time, it is also equipped with auxiliary systems such as air supply device and substrate auxiliary temperature control system.

[0051] The amorphous alloy powder material is zirconium-based amorphous alloy Zr 41.2 Ti 13.8 Cu 12.5 Ni 10 Be 22.5 Powder, D 50 =15-53μm; Specifically, zirconium-based amorphous alloys have high glass-forming ability and thermal stability, which can inhibit the crystallization caused by heat accumulation during additive manufacturing. For this reason, zirconium-based amorphous alloys are preferred for forming process experiments in this research. The raw materials for SLM metal laser additive manufacturing are metal powders, and there are many types of zirconium-based amorphous alloys. This research selected the powder (D) of zirconium-based amorphous alloy (Zr41.2Ti13.8Cu12.5Ni10Be22.5) produced by Panxing New Alloy Materials Co., Ltd. 50 =15-53μm) as the test raw material.

[0052] The additive manufacturing substrate uses a metal zirconium plate. Specifically, the substrate serves as the supporting part of the laser additive manufacturing experimental sample, which indirectly determines the forming quality of the printed sample. It is crucial to choose a suitable substrate material. Usually, the printing substrate for laser additive manufacturing is a stainless steel substrate. However, due to the large difference in performance between zirconium-based amorphous alloys and stainless steel substrate materials, it is very easy to produce elemental dissolution in the initial layer of forming, resulting in failure of amorphous forming. Therefore, the metal zirconium plate with excellent comprehensive performance is selected as the substrate material, mainly because the metal zirconium plate has a high thermal conductivity of about 14 to 21W / mK, which can ensure that the high heat generated by the processing layer during laser printing can be quickly transferred, which is conducive to the formation of the amorphous phase of the processing layer; secondly, because the Zr-based powder and the metal zirconium substrate have excellent wettability, the two are excellently metallurgically bonded during printing; in addition, metal zirconium also has excellent yield strength and hardness.

[0053] The laser power was 90 W, the scanning rate was 1000 mm / s, and the inter-layer scanning angle was 0°.

[0054] The scanning rate was selected as 1000mm / s, the printing layer thickness angle was 20μm, and the laser powers of 80W, 90W and 100W were used to prepare zirconium-based amorphous alloy samples, respectively. The microstructure morphology of the samples after corrosion was observed using an optical microscope. As can be seen from the figure, the sample prepared with a power of 90W has the lowest degree of crystallization, a relatively dense structure, no cracks on the surface, only a small number of holes and defects with a diameter of less than 50μm, and no obvious morphology and structural characteristics of the sample, which is consistent with the structural characteristics of amorphous alloys. When the power was reduced to 80W, many dark and elongated structures appeared in the sample, indicating that crystallization occurred in this area, and the number and size of holes and defects increased. When the power was 100W, the sample had the highest density, no obvious holes and defects were found, and the bottom layer of the sample had no obvious morphology and structural characteristics, but an obvious molten pool shape and a continuous peak-shaped heat-affected zone appeared in the upper layer of the sample, indicating that more serious crystallization occurred. Therefore, the laser power was finally selected as 90W.

[0055] The laser power was selected as 90W, the printing layer thickness angle was 20μm, and the scanning rates of 1200mm / s, 1000mm / s and 800mm / s were used to prepare zirconium-based amorphous alloys. According to the microstructures of zirconium-based amorphous alloys prepared at different laser scanning rates, it can be obtained that the amorphous alloys at each scanning rate have obvious molten pool shapes. When the scanning rate is 1200mm / s, there are no obvious morphological and structural features inside the molten pool. As the scanning rate decreases, the heat-affected zone is significantly widened and the degree of crystallization rapidly deepens. When the laser scanning rate is 1000mm / s, there is still no obvious crystallization area inside the molten pool, and the density of the sample is high, indicating that the forming quality of the amorphous alloy is good at this scanning rate. However, when the scanning rate is 800mm / s, crystallization occurs in the molten pool. This is because when the scanning rate is low, the violent flow of the molten pool will bring the crystallized phase in the heat-affected zone adjacent to the molten pool into the molten pool. Therefore, the laser scanning rate was finally selected as 1000mm / s.

[0056] In the laser additive manufacturing process, the scanning strategy has the most important impact on the unit energy density. Therefore, the scanning strategy is crucial for the forming of amorphous alloys. The most direct scanning strategy is to change the interlayer scanning angle. The interlayer scanning angle refers to the angle between the directions of laser travel when adjacent deposited layers are formed. The laser additive manufacturing process is a point-by-point melting and deposition process. The deposited layer will produce a complex thermal cycle history due to different laser scanning strategies, which directly affects the forming of amorphous alloys. Changing the interlayer scanning angle is the simplest and most feasible method to change the laser scanning strategy. Studying its influence on the microstructure of zirconium-based amorphous alloys is of great significance to improving the forming quality of amorphous alloys. Therefore, the amorphous printing quality using a 0° scanning angle is better.

[0057] S3, integration of amorphous alloy ultra-wideband antenna: adjust the angle and place the antenna according to its structural characteristics and print it;

[0058] The ultra-wideband antenna is printed at a 45° angle, which also avoids warping and cracking caused by excessive thermal stress generated by large-area laser scanning.

[0059] Selective laser melting (SLM) uses a highly collimated high-power laser beam to melt metal powder layer by layer. During this process, a metallurgical bond is formed between the molten materials. Due to the advantages of SLM, some research activities have been carried out to explore the feasibility of using SLM to manufacture BMGs. However, there are still some shortcomings. Previous studies have some disadvantages: (a) defects such as pores lead to low relative density, (b) the formed samples are amorphous composite structures rather than pure amorphous, and (c) critical size is limited. Ultra-large and high-quality Zr-based BMGs are very important for the comprehensive promotion and use of BMGs. The present invention uses the previously optimized parameters to optimize the Zr 41.2 Ti13.8 Cu 12.5 Ni 10 Be 22.5 An attempt was made to break through the size limitation and an ultra-large Zr-based amorphous alloy space microwave component was successfully prepared, with an overall size of 74mm in length, 74mm in width and 32mm in height.

[0060] After preliminary exploration of process parameters, the amorphous rate and mechanical properties of the sample were used as measurement indicators. The optimal process parameters were as follows: power: 90W, scanning rate: 1000mm / s, scanning spacing: 0.07mm, layer thickness: 0.03mm, and inter-layer rotation angle: 0°. In order to minimize support, the microwave component was printed at a 45° tilt, which also avoided warping and cracking caused by excessive thermal stress caused by large-area laser scanning. The printed microwave component is as follows: Figure 4 shown.

[0061] Observation and study of the formed samples show that all models are well formed, with no obvious macro defects, no cracks or burning phenomena, and it can be seen from the figure that the formed samples have good metallic luster.

[0062] The sample was cut from the substrate using wire cutting and then sandblasted. Figure 4 As shown, the left picture is the support structure, and the right picture is a schematic diagram of removing the support structure. For the processed microwave antenna, the physical sampling method is used to test the performance of the printed Zr-based amorphous alloy microwave component. Five different areas are selected from the microwave component to test the corresponding amorphous rate and mechanical properties to ensure the reliability of the results.

[0063] S4, 3D printed amorphous alloy ultra-wideband antenna test verification:

[0064] The printed amorphous alloy antenna is subjected to structural tests, amorphous rate tests, electrical performance tests, and high and low temperature electrical performance tests to complete the antenna performance verification. Specifically, an optical scanning measurement system is used to test the dimensional accuracy of the printed amorphous alloy antenna; a D8 ADVANCE A25 X-ray diffractometer is used to detect the amorphous rate of the printed amorphous alloy antenna, with a scanning step of 0.02°, a scanning speed of 1° per minute, and a scanning range from 20° to 90°; a dual cable connection is used to test the electrical performance of the printed amorphous alloy antenna; a DELTA9023 is used to test the conductivity of the printed amorphous alloy antenna at five temperature environments: -120°C, -50°C, 0°C, 100°C, and 170°C. More specifically, S4 includes:

[0065] S4.1, Dimensional accuracy measurement of amorphous alloy ultra-wideband antenna components: This invention uses an optical scanning measurement system to test the key dimensional accuracy of the printed ultra-wideband antenna components. By comparing with the design model and characterizing the micro-area at the edge of the amorphous component, such as Figure 5 As shown, the key positions were measured and characterized, and it was found that the maximum deviation of the additive manufacturing line width of the amorphous alloy was +46μm, and the required accuracy was better than 50μm.

[0066] S4.2, amorphous rate test of amorphous alloy ultra-wideband antenna components: Each heat input in selective laser melting will cause a heat-affected zone, which is likely to cause crystallization, and the ultra-large-scale printing process will cause the already formed lower structure to be repeatedly heated, which is very likely to cause sample crystallization. Although ultra-large-scale amorphous space microwave components have been successfully prepared under this forming parameter, it is still not guaranteed that a completely amorphous ultra-large-scale bulk amorphous alloy can be prepared. Therefore, it is very necessary to detect the amorphous content in different areas of the ultra-large-scale sample. The D8 ADVANCE A25 X-ray diffractometer was used to detect the amorphous rate of the component, with a scanning step of 0.02°, a scanning speed of 1° per minute, and a scanning range of 2θ angle from 20° to 90°. The amorphous rate is the ratio of the area S1 occupied by the amorphous to the total area S1+S2, that is, the amorphous rate = S1 / (S1+S2). After calculation, it is obtained that the overall average amorphous rate of the prepared amorphous alloy microwave components is above 96%, reaching an almost completely amorphous state, which meets the requirements for the amorphous content of the amorphous alloy, and the required amorphous rate is 96%.

[0067] S4.3, electrical performance test of amorphous alloy ultra-wideband antenna components: For 3D printed amorphous alloy antenna components, because the antenna is a dipole antenna, a dual cable connection is required for testing.

[0068] For the differential dipole antenna, its transmission parameter sd11 and voltage standing wave ratio VSWR need to take into account the coupling effect of the dipole: Therefore, its differential echo characteristic parameters can be expressed as:

[0069] sd11=10*log10(((re(S(1,1))-re(S(1,2)))*(re(S(1,1))-re(S(1,2)))+(im(S(1,1))-im(S(1,2)))*(im(S(1,1))-im(S(1,2)))))

[0070] The corresponding differential voltage standing wave ratio characteristic parameter can be expressed as:

[0071] VSWR_sd11=(1+sqrt(((re(S(1,1))-re(S(1,2)))*(re(S(1,1))-re(S(1,2)))+(im(S(1,1))-im(S(1,2)))*(im(S(1,1))-im(S(1,2) ))))) / (1-sqrt(((re(S(1,1))-re(S(1,2)))*(re(S(1,1))-re(S(1,2)))+(im(S(1,1))-im(S(1,2)))*(im(S(1,1))-im(S(1,2))))))

[0072] According to the measured S parameter vector results, the differential echo sd11 and differential voltage standing wave ratio VSWR_sd11 characteristics of the dipole antenna can be calculated, such as Figure 6 As shown:

[0073] From the results in the above figure, it can be seen that, calculated at -10dB, the working bandwidth of the antenna is 2.52GHz to 4.55GHz, and the relative bandwidth reaches 58%.

[0074] S4.4, High and low temperature electrical properties test of amorphous alloys: For the electrical properties test of amorphous alloys in high and low temperature environments, the test piece is placed in an incubator for a period of time (30 minutes), different temperatures are set, and then the surface conductivity characteristics of the amorphous alloy at different frequencies are tested.

[0075] In order to clarify the influencing mechanism of the mechanical properties of amorphous alloys after experiencing extreme high and low temperature conditions in space, tests on the electrical properties and mechanical structural strength properties of amorphous alloys under extreme temperature conditions were carried out.

[0076] For the conductivity test of amorphous alloy materials under extreme temperatures, DELTA9023 was used to test the conductivity of amorphous alloys in five temperature environments: -120℃, -50℃, 0℃, 100℃, and 170℃.

[0077] From the test results, the conductivity of amorphous alloys slightly decreases with temperature at 8 GHz and 18 GHz, from 0.61 to 0.59 MS / m and from 0.39 to 0.37 MS / m respectively. This is because, for amorphous materials, the same high temperature increases the phonon energy inside the material, causing electrons to consume more energy and interact with phonons during migration, reducing conductivity.

[0078] Therefore, in order to maintain the stability of the amorphous alloy antenna in high and low temperature environments, the conductivity of the amorphous alloy does not change with temperature by more than 10% in the five temperature environments of -120°C, -50°C, 0°C, 100°C, and 170°C within the operating frequency range.

[0079] Specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical solution of this application fall within the protection scope of the present invention.

[0080] Embodiment 1:

[0081] This embodiment provides a design and manufacturing method of an ultra-wideband amorphous alloy antenna based on 3D printing, which specifically includes:

[0082] (1) Design the geometry of the ultra-wideband antenna, including the folded bow structure and the center feed ring.

[0083] (2) Design optimization of dipole antenna for 3D printing. Considering that the side wall of the substrate will greatly affect the molding quality, the side wall is removed and the optimized design thickness of the folded bow structure is 1 mm.

[0084] (3) SLM metal laser additive manufacturing equipment is used. The equipment uses a 200W continuous laser, the galvanometer scanning system is a three-axis high-precision scanning galvanometer, and the laser is controlled by a digital signal. The laser spot diameter is 20-100μm and the maximum scanning speed is 15m / s; the molding cylinder size is a Φ150mm cylindrical molding cylinder, the molding height is 200mm, the powder layer thickness is 0.02-1.00mm adjustable, the specific powder thickness is 30um, the powder feeding method is unidirectional powder feeding, and the printing powder is selected as zirconium-based amorphous alloy (Zr 41.2 Ti 13.8 Cu 12.5 Ni 10 Be 22.5 ) powder (D 50 =15~53μm) is used as the printing raw material, and the metal zirconium plate with excellent comprehensive performance is selected as the substrate material.

[0085] (4) The printing parameters were optimized according to the printing defects, printing quality and amorphous ratio. The scanning rate was selected as 1000 mm / s, the laser power was 90 W, and the scanning strategy was: the inter-layer scanning angle was 0°.

[0086] (5) The microwave component is printed at an angle of 45°, annealed after printing, and the support is removed; in order to minimize the support, the microwave component is printed at an angle, which also avoids warping and cracking caused by excessive thermal stress generated by large-area laser scanning.

[0087] (6) An optical scanning measurement system is used to test the critical dimensional accuracy of the printed ultra-wideband antenna components, requiring the maximum structural deviation to be less than 50um.

[0088] (7) The 3D printed amorphous alloy antenna component is connected by dual cables to test its transmission parameters sd11 and voltage standing wave ratio VSWR. The coupling effect of the dipole should be considered, and the relative bandwidth of the sd11 echo characteristic is required to be greater than 50% under the requirement of -10dB. Specifically, for the 3D printed amorphous alloy antenna component, because the antenna is a dipole antenna, a dual cable connection is required for testing. For the differential dipole antenna, its transmission parameters sd11 and voltage standing wave ratio VSWR should consider the coupling effect of the dipole.

[0089] (8) Use an incubator to place the test piece for a period of time (30 minutes) and set different temperatures (using DELTA9023, the conductivity of the amorphous alloy is tested in five temperature environments: -120°C, -50°C, 0°C, 100°C, and 170°C). Then, test the surface conductivity characteristics of the amorphous alloy at different frequencies, requiring that the conductivity change with temperature should not exceed 10%.

[0090] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0091] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0092] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A design and manufacturing method of an ultra-wideband amorphous alloy antenna based on 3D printing, characterized in that: The following steps are involved: S1, Optimization design of space microwave components for integrated additive manufacturing: The space microwave component is an ultra-wideband antenna, and the structure and thickness of the ultra-wideband antenna are designed and optimized; S2, the realization parameters of high-strength amorphous alloys based on selective laser melting additive manufacturing: determine the equipment for additive manufacturing, amorphous alloy powder materials and additive manufacturing substrates, as well as laser power, scanning rate and scanning strategy; S3, integration of amorphous alloy ultra-wideband antenna: adjust the angle and place the antenna according to its structural characteristics and print it; S4, 3D printed amorphous alloy ultra-wideband antenna test verification: Perform structural tests, amorphous rate tests, electrical performance tests, and high and low temperature electrical performance tests on the printed amorphous alloy antenna to complete antenna performance verification.

2. The design and manufacturing method of the ultra-wideband amorphous alloy antenna based on 3D printing according to claim 1, characterized in that: In S1, the ultra-wideband antenna includes a folded bow structure and a central feeding ring; The folded arched structure serves as an electric dipole, comprising two inclined plane parts symmetrically distributed on the left and right and horizontal parts connected to the distal ends of the two inclined plane parts, wherein the connection between the horizontal part and the inclined plane part is the downwardly inclined end of the inclined plane part; The central feeding ring serves as a magnetic dipole and includes two short-circuit walls, a ground between the two short-circuit walls, and the bottom surfaces of the two inclined portions; the short-circuit wall is connected to the lower end where the inclined portion and the horizontal portion meet, and the two short-circuit walls are opposite to each other.

3. The design and manufacturing method of the ultra-wideband amorphous alloy antenna based on 3D printing according to claim 2, characterized in that: The thickness of the folded arched structure is 1 mm.

4. The design and manufacturing method of the ultra-wideband amorphous alloy antenna based on 3D printing according to claim 1, characterized in that: In S1, the ultra-wideband antenna is excited by a pair of differential feed lines, which are composed of two sections of 50-Ω microstrip lines and a tapered parallel strip transmission line; one end of each 50-Ω microstrip line is connected to an SMA connector, and the other end is connected to the tapered parallel strip transmission line; the tapered parallel strip transmission line realizes an impedance transformer between 100Ω and 212Ω.

5. The design and manufacturing method of the ultra-wideband amorphous alloy antenna based on 3D printing according to claim 1, characterized in that: In S2, the additive manufacturing equipment uses SLM metal laser additive manufacturing equipment, which uses a 200W continuous laser, the galvanometer scanning system is a three-axis high-precision scanning galvanometer, and the laser is controlled by digital signals. The laser spot diameter is 20 to 100 μm and the maximum scanning speed is 15 m / s.

6. The design and manufacturing method of the ultra-wideband amorphous alloy antenna based on 3D printing according to claim 1, characterized in that: In S2, the amorphous alloy powder material is a zirconium-based amorphous alloy Zr 41.2 Ti 13.8 Cu 12.5 Ni 10 Be 22.5 Powder, D 50 =15-53μm.

7. The design and manufacturing method of the ultra-wideband amorphous alloy antenna based on 3D printing according to claim 1, characterized in that: In S2, the additive manufacturing substrate is a metal zirconium plate.

8. The design and manufacturing method of the ultra-wideband amorphous alloy antenna based on 3D printing according to claim 1, characterized in that: In S2, the laser power is 90 W, the scanning rate is 1000 mm / s, and the inter-layer scanning angle is 0°.

9. The design and manufacturing method of the ultra-wideband amorphous alloy antenna based on 3D printing according to claim 1, characterized in that: In S3, the ultra-wideband antenna is printed at an angle of 45°.

10. The design and manufacturing method of the ultra-wideband amorphous alloy antenna based on 3D printing according to claim 1, characterized in that: The S4 includes: using an optical scanning measurement system to test the dimensional accuracy of the printed amorphous alloy antenna; using a D8 ADVANCE A25 X-ray diffractometer to detect the amorphous rate of the printed amorphous alloy antenna, with a scanning step of 0.02°, a scanning speed of 1° per minute, and a scanning range from 20° to 90°; using a dual cable connection to test the electrical performance of the printed amorphous alloy antenna; using DELTA9023 to test the conductivity of the printed amorphous alloy antenna at five temperature environments of -120°C, -50°C, 0°C, 100°C, and 170°C.